Serum Clusterin Level Associated with Post-ischemic Stroke Cognitive Dysfunction - Herpan Syafii Harahap; Yanna Indriyana; Sri Budhi Rianawati; Eko Arisetijono; Arina Windri Rivarti (Jurnal Kesehatan Masyarakat, 2025)
The exploration of potential blood-based biomarkers that could be useful in the early detection of cognitive impairment associated with ischemic stroke is still being studied. The objective of this study was to examine the correlation between serum clusterin levels and the prevalence of cognitive impairment in individuals with ischemic stroke. A total of 86 outpatients with mild ischemic stroke within the first three months of its onset were recruited from three primary hospitals in Mataram, Indonesia. ELISA was used to measure the serum clusterin level. Patients’ sociodemographic and clinical data were also collected as covariates. The Montreal Cognitive Assessment-Indonesian version (MoCA-INA) instrument was used to evaluate cognitive status. The study used multivariate logistic regression analysis to investigate the effect of clusterin on the occurrence of cognitive impairment associated with ischemic stroke while controlling for other variables. Results: The multivariate logistic regression analysis revealed a significant correlation between elevated serum clusterin levels and a higher prevalence of cognitive impairment in ischemic stroke patients (odds ratio [OR] 3.56, 95% confidence interval [CI] 1.04-12.16, p = 0.043). Conclusion: Elevated serum clusterin levels have been associated with a higher occurrence of cognitive impairment in ischemic stroke patients.